The Influence of Green Advertising, Green Products, and Social Media on Purchasing Decision - Sariah; Halik, Abdul; Prastiwi, Estik Hari (PT Inovasi Pratama Internasional, 2024)
Problems regarding the environment are starting to become one of the main factors of concern to society today. Likewise, there are various steps taken by the government to overcome environmental problems, such as creating policies stating that companies must produce environmentally friendly products. The purpose of this research is to determine the influence of Green Advertising, Green Products, Social Media on purchasing decisions for Starbucks Coffee Surabaya consumers. This research uses quantitative methods with primary data sources obtained from distributing questionnaires via Google Forms. The research population is the people of Surabaya who have purchased Starbucks products. The selection of respondents was carried out using a non-probability sampling method with a total of 100 respondents based on the Lemeshow formula calculation. The data analysis method uses descriptive analysis and SPSS analysis. The research results show that the variables Green Advertising, Green Product, Social Media have a positive and significant effect on purchasing decisions for Starbucks Coffee Surabaya consumers.